An Autopsy Based Study of Sexual Dimorphism of Adult Human Sterna - Bhumesh Darade1 , Pawan Sabale2 , Shailesh Mohite3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Creation of an individual’s biological profile is of extreme importance and depends on age, sex and stature. The cranial and pelvic bones are important in identifying the sex of an individual. However, loss of complete bones or bones getting destroyed renders it impossible to use them for such estimations. However, since such sex-specific bones are hard to find at each and every scene, forensic experts are left with no choice but to depend on less sexually dimorphic elements of the human skeleton such as the sternum. This study was conducted in subjects that were subjected to medicolegal autopsy. The deceased aged 18 years and above, of either sex, were included in study. The deceased with evidence of trauma and surgery to the anterior chest wall, generalized bone diseases, observable deformities over the sternum were excluded. The analysis of 300 sterna was carried out to study sexual dimorphism in sternum using different parameters such as width of suprasternal notch, width of sternum at level of fourth rib, posterior curved length of sternum, manubrio-corpus index and length of sternum.